O discurso narrativo na hipermídia - Pace, Savana (2007)
This work proposes the study of the discourse in the hypermedia, which has its syntactic and semantic relationships reformulated by the interactive potential through the programming. Besides, some of the concepts presented are relative to the reading of the hypermedia ambient, including questions about interactivity and fusion of verbal and non-verbal signs (intersign), the role of reader and the authorship in the digital, and the programming like an expanded writing.